A rare case of incidental mucinous adenocarcinoma with osseous metaplasia associated with cysts of the presacral space - Dionigi Lorusso; Stefania De Santis; Giulio Lantone; Raffaele Armentano (Turkish Journal of Gastroenterology, 2019)
Cite this article as: Lorusso D, De Santis S, Lantone G, Armentano R. A rare case of incidental mucinous adenocarcinoma with osseous metaplasia associated with cysts of the presacral space. Turk J Gastroenterol 2019; 30(5): 495-6.